Efektivitas Kompres Bawang Merah terhadap Nyeri Sendi pada Lansia - Fadlilah, Siti; Widayati, Ririn Wahyu (Politeknik Kesehatan Tanjungkarang, 2018)
One of the changes in the musculoskeletal system such as changes in muscles and joint bones is the most common among the elderly aged > 60 years. The percentage of the joint pain among the elderly in the special region of Yogyakarta is 25.4%. If not treated immediately the incidence rate of the joint disease will increase significantly. This can be overcome by providing an intervention in the form of onion compress. The result of a preliminary study indicated that 22 elderly people experienced the joint pain. The objective is to investigate the effectiveness of onion compress in the joint pain among the elderly in Sanggrahan Hamlet, Wedomartani, Ngemplak, Sleman, Yogyakarta. Research Method is this was a quantitative study, namely a quasi-experimental study. The sample consisted of 15 people. The sampling technique was the purposive sampling technique. The measurement instrument was the pain ratio scale. The statistical test was the Wilcoxon signed rank test. Results are The mean scores of the pain scale before and after onion compress were 5.2 and 2.4 with a mean difference of 2.8. The bivariate test yielded p-value=0.001. Conclusion and Suggestion are Onion compress is effective to decrease the joint pain among the elderly in Sanggrahan Hamlet, Wedomartani, Ngemplak, Sleman, Yogyakarta. The respondents are expected to be able to apply an onion compress as a complementary therapy for the joint pain.